2009
DOI: 10.1007/s00531-009-0450-4
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic field anomalies over the Lombok Island region: an attempt to understand the local tectonic changes

Abstract: During the last years, several investigations on the earthquakes and related tectonic structures along the Java trench have been conducted. In this study, we focus on the Lombok Island -West Nusa Tenggara (Indonesia), which lies between the centres of the highest intensity of contiguous negative-positive geomagnetic anomalies in this region. The geological and tectonic structures, however, are not known in detail for this island, whereas a better knowledge of these conditions could lead to better estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The schematic model in Figure 12 extends a similar model on the Lombok Island that describes the topographic evolution of this island from the Late Oligocene to the Holocene (Zubaidah, 2010). Although only focused on the western part (SW direction from caldera), our model further develops the previously proposed model yet with a higher resolution, especially the recent evolution over the last ~700 years.…”
Section: Discussionmentioning
confidence: 74%
“…The schematic model in Figure 12 extends a similar model on the Lombok Island that describes the topographic evolution of this island from the Late Oligocene to the Holocene (Zubaidah, 2010). Although only focused on the western part (SW direction from caldera), our model further develops the previously proposed model yet with a higher resolution, especially the recent evolution over the last ~700 years.…”
Section: Discussionmentioning
confidence: 74%
“…Based on the 1978 Flores earthquake and gravity data, McCaffrey and Nabelek (1984) found evidence of a 30 • dipping southward active thrusting of the FOC beneath Lombok, which also confirmed by seismic velocity tomography of Widiyantoro et al (2011). From the gravity regional study done on Lombok Island, a high Bouguer gravity anomaly of around 140 mGal was found northeast of the Rinjani volcano, which can be interpreted as the expression of an igneous rock or magmatic conduit (Sukardi, 1979;Zubaidah et al, 2010). Afif et al (2020) in their recent tomographic velocity study revealed that most of the significant earthquakes occurred at the edge of a high-velocity region where the stress concentration is expected to be the highest.…”
Section: Previous Geological and Geophysical Studiesmentioning
confidence: 83%
“…Limited geophysical surveys have been conducted for Lombok to constrain crustal structure using geomagnetic field observation (Zubaidah et al, 2009) and integrated modeling of gravity and magnetic anomalies (Zubaidah et al, 2014). Because the physical origin associated with tectonic activities which causes the observed potential field anomalies is not as obvious and direct as seismic waves induced by tectonic events such as earthquakes, studies using seismological methods are often better suited to obtaining hazard-relevant information.…”
Section: Introductionmentioning
confidence: 99%